Human Leukocyte Antigen (HLA) B27 Allotype-Specific Binding and Candidate Arthritogenic Peptides Revealed through Heuristic Clustering of Data-independent Acquisition Mass Spectrometry (DIA-MS) Data - Schittenhelm, Ralf B. (Mol Cell Proteomics, 2016)
Expression of HLA-B27 is strongly associated with ankylosing spondylitis (AS) and other spondyloarthropathies. While this is true for the majority of HLA-B27 allotypes, HLA-B*27:06 and HLA-B*27:09 are not associated with AS. These two subtypes contain polymorphisms that are ideally positioned to influence the bound peptide repertoire. The existence of disease-inducing peptides (so-called arthritogenic peptides) has therefore been proposed that are exclusively presented by disease-associated HLA-B27 allotypes. However, we have recently demonstrated that this segregation of allotype-bound peptides is not the case and that many peptides that display sequence features predicted to favor binding to disease-associated subtypes are also capable of being presented naturally by protective alleles. To further probe more subtle quantitative changes in peptide presentation, we have used a combination of data-independent acquisition (DIA) and multiple reaction monitoring (MRM) mass spectrometry to quantify the abundance of 1646 HLA-B27 restricted peptides across the eight most frequent HLA-B27 allotypes (HLA-B*27:02-HLA-B*27:09). We utilized K means cluster analysis to group peptides with similar allelic binding preferences across the eight HLA-B27 allotypes, which enabled us to identify the most-stringent binding characteristics for each HLA-B27 allotype and further refined their existing consensus-binding motifs. Moreover, a thorough analysis of this quantitative dataset led to the identification of 26 peptides, which are presented in lower abundance by HLA-B*27:06 and HLA-B*27:09 compared with disease-associated HLA-B27 subtypes. Although these differences were observed to be very subtle, these 26 peptides might encompass the sought-after arthritogenic peptide(s).